Nucleation of superlattice intrinsic stacking faults via cross-slip in nickel-based superalloys. (December 2022) - León-Cázares, F.D.; Schlütter, R.; Monni, F.; Hardy, M.C.; Rae, C.M.F.
Graphical abstract: Abstract: Superlattice intrinsic stacking faults (SISF) are the main culprit for the low temperature creep deformation of modern nickel-based superalloys used in jet engines. While these faults were identified over fifty years ago, their nucleation mechanism remains unclear. This work provides the first ever experimental evidence, via transmission electron microscopy, of a SISF nucleating from a cross-slip event in a polycrystalline alloy. Such an instance was identified in a grain with a near- 〈 001 〉 tensile loading orientation. In the nucleation mechanism proposed, cross-slip allows the two dissimilar a 2 〈 110 〉 dislocations required to form a SISF to meet on adjacent planes at a precipitate interface. The concept of a nascent fault is introduced: the initial stacking fault that forms on a crystallographic plane and the dislocations of which continue to form coplanar faults as they glide away. This nucleation mechanism and the subsequent dislocation evolution are detailed taking into consideration the shear stresses on the individual Shockley partials and the full dislocations involved, as well as the stress orientation dependence of the energy barrier for cross-slip. These findings will guide future characterisation efforts in the field and inform the modelling of more realistic predictive models of creep behaviour.